Capturing minds: Towards a methods critique of questionnaire-based mental health surveys. (October 2022) - Wackers, Ger; Schille-Rognmo, Marthe
Mental health surveys of general populations use psychometric instruments derived from psychiatric symptom checklists and assessment scales. Mental health surveys of this type have become so ubiquitous and influential that the psychometric methods that are at the heart of them seem to be beyond reproach. Are these the right tools to do the job of capturing the minds of general populations? This article pursues a critical assessment of psychometric instruments embedded in mental health surveys through a historical reconstruction of the major epistemic shifts in the investigative practices through which these psychometric instruments developed. The reconstruction traces a strong influence of physics and physicists' notion of fundamental measurement of quantities on psychologists' attempts to measure mental phenomena. Surveys employing these instruments inherit unresolved methodological issues from their psychophysical predecessors: problems of causal inference from mathematical abstractions (correlations) and reification of mental entities from theoretical concepts.